.5(.5x-1)=-4.5

Simple and best practice solution for .5(.5x-1)=-4.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .5(.5x-1)=-4.5 equation:



.5(.5x-1)=-4.5
We move all terms to the left:
.5(.5x-1)-(-4.5)=0
We add all the numbers together, and all the variables
.5(.5x-1)+4.5=0
We multiply parentheses
0.5x-0.5+4.5=0
We add all the numbers together, and all the variables
0.5x+4=0
We move all terms containing x to the left, all other terms to the right
0.5x=-4
x=-4/0.5
x=-8

See similar equations:

| -5x-8x-12=-9x-x | | 2)4x+2)=4x-12(x-1) | | 6y+2-4=6y | | 4(x+1)-3=1+(x-6) | | 9x-9/15=3x+18/12 | | 7x+4-2x=9x+4 | | 9x+1=8x-1 | | 5w+8-12w=12-15w | | (2w-4)^2=36 | | 45x+2=6x | | 3+5/8x=1/4 | | (x+1)^4/3=81 | | 5+2x+2x=x-7 | | 17-2r=1 | | 18n-19=5n+5 | | 9^x=27^2-2x | | .50x(4)=1.00x(6) | | -91+13x=63+6x | | -2a–3a+-20=-5 | | 2(4-2x)+4=-8 | | 5x/2-1=x+1/4 | | 2(4z−1)=3(z+2)2(4z−1)=3(z+2) | | 4(1.4c+6)-2c=-9 | | 6y+12-4=6y | | 6-a/2=8 | | (6x/(x+3)(x-1))/(3/(x+3))=1 | | 1/1.4=x/x+1 | | 14.69+0.07h=15.19+0.15h | | 135=7x+11x+9 | | -2=n-4+1 | | 4x+6=8+2x | | 28+22.75m=50+17.25m |

Equations solver categories